Continuous vancomycin infusion versus intermittent infusion in critically Ill patients: The research protocol - Maluangnon, Chailat; Permpikul, Chairat (Clinical Critical Care, 2022)
Background: Methicillin‐resistant Staphylococcal and Enterococcal infections are important problems in intensive care units (ICUs). Vancomycin is a drug of choice, and continuous administration has long been proposed as an alternative method with better therapeutic benefits. This study aims to examine information on the benefits of continuous vancomycin infusion (CVI) compared with the intermittent vancomycin infusion (IVI) method. Method: A quasi-experimental study with a propensity score-matched historical control involves adult patients in medical or surgical ICUs. In the experimental group, 31 patients for whom vancomycin is indicated will be enrolled to receive CVI for at least 48 hours with therapeutic drug monitoring according to the study protocol. For the historical control group, data of patients who received IVI between January 2018 and October 2020 will be retrospectively reviewed. Capability to achieve serum vancomycin therapeutic target within 48 hours, 96 hours, the incidence of supra- and subtherapeutic level, treatment successfulness, mortality, and incidence of acute kidney injury (AKI) between the two infusion methods will be analyzed before and after one-to-two propensity score matching. Ethics and dissemination: The study was approved by the institutional review boards of Faculty of Medicine Siriraj Hospital, Mahidol University (COA no. Si 027/2021). We plan to disseminate the results in peer-reviewed critical care medicine or infectious disease-related journals and national and international conferences. Trial registration: TCTR20210122005. Registered on January 22, 2021, with Thai Clinical Trials Registry